Disparity between knowledge and practice regarding COVID-19 in Thailand: A cross-sectional study of older adults - Paolo Miguel Manalang Vicerra (PLoS ONE, 2021)
The efficacy of the public health measures to mitigate COVID-19 is influenced by health literacy which includes the level of knowledge about the disease and the preventive behaviours adopted by individuals. Thailand, being a low- and middle-income country with an ageing society, has to consider both the challenges that its health system has in disseminating information and the disparities in health literacy among its older population. This study investigated the knowledge and behaviour of older adults in Thailand regarding COVID-19 using the Impact of COVID-19 on Older Persons in Thailand, a cross-sectional survey. The data was primarily collected online and included 1,230 adults aged at least 60 years from nine provinces of the five regions of the country. The associated factors with the health literacy outcomes were tested using bivariate logistic regression analyses. It was observed that 43% of the older adults in the sample had proper knowledge of the disease and 33% adopted preventive behaviours. Knowledge about the disease was not associated with preventive behaviour. The associated factors common between the increased levels of knowledge and adoption of behaviours were rural area residence and higher educational attainment levels. Obtaining information from the internet was observed to increase knowledge while having the television and radio as sources of information had negative relationship. Many older adults continued to be employed during the lockdown period and this was associated with decreased adoption of preventive behaviour. The context of vulnerable populations, particularly older adults, is different with regard to their access to information and concern about income. Health information has to be tailored for targeted populations. Their needs also have to be addressed as they have increased risks because of financial and health susceptibilities.